Pola Pengobatan Pasien Hipertensi di Puskesmas X Kabupaten Kudus - Muslim, Ahmad Suriyadi; Rahmawati, Riana Putri; Sugiarti, Retno; Sari, Fatika; Amalia, Linda (SAMODRA ILMU: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2024)
Background: According to the WHO, hypertension is a degenerative disease suffered by the majority of the world's population. Meanwhile, in Indonesia itself, the number of people suffering from hypertension increased by 25.8%. If left untreated, hypertension can cause various other diseases such as stroke, heart attack, and diabetes mellitus. Method: This study aims to determine the treatment patterns of hypertensive patients at Puskesmas Rejosari, Kudus Regency. This type of research is a non-experimental descriptive study using a retrospective approach with patient data from July to September 2024. Research Results: The results of the study show that the prevalence of anti-hypertensive medication use in the CCBs group with amlodipine was 50%, the ACE Inhibitor group with captopril was 20%, the use of Hydrochlorothiazide (HCT) was 10%, furosemide was 5%, and the use of combination therapy was 15%. Conclusion: The antihypertensive medication utilization pattern among hypertensive patients at the Puskesmas primarily involves the use of CCB (Amlodipine) as the first-line treatment. The effective and safe use of antihypertensive medications can contribute to blood pressure control and the prevention of hypertension-related complications.